WOMEN AS CUSTODIANS OF FOLK ART TRADITIONS IN INDIA: GENDERED NARRATIVES AND CULTURAL CONTINUITIES IN CONTEXT TO MADHUBANI ART OF BIHAR - Jha, Aditi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Folk art in India embodies centuries of collective memory, community identity, and cultural resilience. Women have historically been the primary custodians of these traditions, transmitting artistic knowledge through domestic practices, ritual expressions, and communal storytelling. This paper explores the gendered dimensions of folk art in India, focusing on how women negotiate tradition and modernity, invisibility and recognition, domesticity and livelihood. Drawing on case studies from Madhubani Art traditions, the study situates women’s artistic agency within feminist theoretical frameworks and cultural anthropology. The research argues that while globalization and commercialization have provided new opportunities for women artists, they have also reshaped the meanings, ownership, and sustainability of folk art practices.